A review on methodologies for extraction, identification and quantification of allergenic proteins in prawns. (July 2019) - Faisal, M.; Vasiljevic, T.; Donkor, O.N.
Abstract: Prawn allergy is one of the most common food-borne allergies and current prevention is by avoidance. This review paper summarised different methodologies for the extraction, identification and quantification of prawn protein allergens, reported in various research studies. Following extraction, allergenic components have been analysed using well-established methodologies, such as SDS-PAGE, Immunoblotting, ELISA, CD Spectroscopy, HPLC, DBPCFC, SPT etc. Moreover, the preference towards Aptamer-based technique for allergenicity analysis has also been highlighted in this review paper. The summary of these methodologies will provide a reference platform for present and future research directions. Graphical abstract: Unlabelled Image Highlights: Effective separation and visualization of proteins depend on SDS PAGE gel concentrations. Sandwich ELISA is more precise than indirect and Inhibition ELISA for allergenicity quantification. Aptamers provides more specific immunogenic reaction for allergens than antibodies. Allergenic proteins can be isolated by reversed-phase, anion-exchange and hydrophobic interaction HPLC methods. This review paper will provide a better platform for present and future research direction on allergenic prawn proteins.